PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PADA KINIKO COFFEE SHOP KINIKO - Rina Rahmawati; Yusuf, Ramayani (Universitas Haji Sumatera Utara, 2023)
With changes in people's lifestyles and increasing incomes, especially urban communities, the growth of the culinary industry is also increasing. The café business has become one of the most popular businesses in the city of Garut in recent years. The purpose of this study is to identify the effect of Sales Promotion on Purchasing Decisions at Coffee Shop Kiniko. The research method used in this study is a quantitative method, with the same population and sampling as many as 100 respondents by distributing questionnaires filled out by randomly selected Kiniko Coffee Shop visitors. The data obtained is analyzed using a data analysis tool, namely SPSS. The results of the data analysis show that Sales Promotion has a significant influence on Purchasing Decisions at Kiniko Coffee Shop. The sales promotion variable positively and significantly influences purchasing decisions with a simple coelation value of 0.674 which means there is a positive influence and has a strong degree of relationship between Sales Promotion and Purchase Decisions. Meanwhile, based on the results of the study, the probability value of Sales Promotion to Purchase Decision is 0.000. Thus, the hypothesis proposed in the study was accepted.